Perras, marginalidad y violencia en el teatro argentino del siglo XXI - Zalba, Rocío (Latin American Theatre Review, 2013)
In this essay I examine the play Perras (2002), a joint work by Néstor Caniglia, Enrique Federman, Mauricio Kartun, and Claudio Martínez Bel, which demonstrates in a crude and bestial way the degeneration and transformation of the marginalized in post-crisis Argentina (2001). It is in the private sphere, where domestic abuse and bestiality occur, that we observe the play’s aggressors unravel in a process of reflexive nostalgia. This nostalgia, as described by Svetlana Boym in The Future of Nostalgia, is a process of personal reflection that meanders through multiple narratives and temporalities, both real and fictitious. The subversive nature of the marginalized being, together with the egocentric and ludic qualities of this introspective nostalgia, leads these aggressors to fail to recognize the violence and perversion of their actions, thereby making them transform into beasts themselves.